Clinico-laboratory profile of 45 filarial arthritis cases - Sarker, PC; Khandker, HH; Sarker, CR; Khatoon, M (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S7-11 The abstract of this article is available on the PubMed website